PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rahayu, Novita Tri; Siregar, Oktarini Khamilah; Maisyarah, Renny (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This research aims to determine the effect of financial performance on share prices with dividend policy as a moderating variable in food and beverage sub-sector manufacturing companies listed on the IDX. This research uses seven independent variables of financial performance with ROA, ROE, CR, DAR, Asset Turnover, NPM, DER protection, with the dependent variables being stock price and dividend policy as moderating variables. The research method used is an associative quantitative method. This research uses linear regression analysis techniques. The population in this study were food and beverage sub-sector manufacturing companies registered on the IDX in the 2018-2022 period and the sampling technique was purposive sampling technique. The results of this research show that there is a simultaneous influence of ROE, CR, DAR, NPM, DER on stock prices, ROA, ROE, CR, DAR, Asset Turnover, NPM, DER have a simultaneous effect on stock prices, DPR is able to moderate ROA, ROE, CR, DAR, Asset Turnover, NPM, DER on share prices and there is no influence of ROA on share prices in food and beverage sub-sector manufacturing companies for the 2018-2022 period.